Transcultural Nursing and Female Circumcision - Heatherly, Jennifer (Operating Room Nurses Association of Canada Journal, 2000)
Two years ago while working in a paediatric operating room I met a young Somalian refu gee girl whose family had only recently immigrated to Canada. The family spoke very little English and had brought their six year old daughter to the hospital to have a urological procedure performed to treat her urethral strictures.